Negative emotional reactivity and maladaptive emotional regulation strategies mediate the prospective relationship between depressive symptoms and insomnia symptoms in individuals with insomnia - Helen Tsz Ching Tsui; Wai Sze Chan (Journal of Affective Disorders Reports, 2024)
Background: Emotional reactivity and regulation have been frequently proposed to explain the relationship between insomnia symptoms and depressive symptoms. However, no longitudinal study has examined insomnia symptoms, depressive symptoms, and emotional reactivity and regulation simultaneously and evaluated the mediating role of emotional reactivity and regulation. The current study investigated emotional reactivity and regulation as potential mediators of the relationship between insomnia symptoms and depressive symptoms in a three-wave longitudinal study over three months. Methods: Nine hundred and twenty-four participants with clinically significant insomnia were recruited (ages ranging from 16 to 69 years, 72.9 % female). They filled out questionnaires that measured insomnia symptoms, depressive symptoms, emotional reactivity, and the use of emotion regulation strategies once per month for three months. Results: The results showed that depressive symptoms predicted insomnia symptoms (but not vice versa) via negative emotional reactivity, rumination, and catastrophizing. Limitations: This study is limited by its attrition rate (52.9 %) and self-report measures. Participants were individuals with insomnia and mainly young, educated adults, so the generalizability of the findings to other populations might also be limited. Conclusions: These novel findings highlighted the importance of targeting emotional processes in assessing and treating individuals with insomnia and depression.